PELATIHAN PROSES PENJURNALAN PERUSAHAAN DAGANG UNTUK SISWA SMA ST. TARSISIUS I - Adang, Ferry; Ivonne Patricia; Jonathan, Michelle Leevia; Sylvia; Theodore Benedict Alvin T (Jurnal Serina Abdimas, 2024)
In facing the era of globalization and increasingly complex business dynamics, trading companies are required to remain competitive and adaptive to market changes. The success of a company is not only determined by the products or services offered but also by its ability to manage finances effectively and efficiently. The introduction of training in the journaling process is expected to make a positive contribution to the quality of education at St. Tarsisius I High School. Students will not only gain theoretical knowledge but also practical skills that they can apply in the future, especially if they choose a career path in accounting. The training for the journaling process in the trading company at St. Tarsisius I High School is conducted through face-to-face sessions 10 times, each lasting 90 minutes. This training activity takes place every Wednesday from 2:30 PM to 4:00 PM. After preparation, the PKM team presents theoretical material followed by discussions of example problems to ensure better understanding among St. Tarsisius I High School students. In this activity, the UNTAR PKM team had the opportunity to conduct training in the journaling process for trading companies at St. Tarsisius I High School. The implementation of the activity has yielded satisfactory and effective results. The quiz results and the enthusiasm of St. Tarsisius I High School students indicate that they have gained more knowledge about the journaling process for trading companies. The result of this activity is the transfer of knowledge regarding basic accounting to St. Tarsisius I also prepares them to become Accounting students in the future. This can be a solution to overcome the problems faced by partners regarding limited time in introducing basic accounting knowledge for high school students.